Improved noninvasive prediction of liver fibrosis by liver stiffness measurement in patients with nonalcoholic fatty liver disease accounting for controlled attenuation parameter values. Issue 4 (5th November 2016) - Petta, Salvatore; Wong, Vincent Wai‐Sun; Cammà, Calogero; Hiriart, Jean‐Baptiste; Wong, Grace Lai‐Hung; Marra, Fabio; Vergniol, Julien; Chan, Anthony Wing‐Hung; Di Marco, Vito; Merrouche, Wassil; Chan, Henry Lik‐Yuen; Barbara, Marco; et al.
Abstract : Liver stiffness measurement (LSM) frequently overestimates the severity of liver fibrosis in nonalcoholic fatty liver disease (NAFLD). Controlled attenuation parameter (CAP) is a new parameter provided by the same machine used for LSM and associated with both steatosis and body mass index, the two factors mostly affecting LSM performance in NAFLD. We aimed to determine whether prediction of liver fibrosis by LSM in NAFLD patients is affected by CAP values. Patients (n = 324) were assessed by clinical and histological (Kleiner score) features. LSM and CAP were performed using the M probe. CAP values were grouped by tertiles (lower 132‐298, middle 299‐338, higher 339‐400 dB/m). Among patients with F0‐F2 fibrosis, mean LSM values, expressed in kilopascals, increased according to CAP tertiles (6.8 versus 8.6 versus 9.4, P = 0.001), and along this line the area under the curve of LSM for the diagnosis of F3‐F4 fibrosis was progressively reduced from lower to middle and further to higher CAP tertiles (0.915, 0.848‐0.982; 0.830, 0.753‐0.908; 0.806, 0.723‐0.890). As a consequence, in subjects with F0‐F2 fibrosis, the rates of false‐positive LSM results for F3‐F4 fibrosis increased according to CAP tertiles (7.2% in lower versus 16.6% in middle versus 18.1% in higher). Consistent with this, a decisional flowchart for predicting fibrosis was suggested by combining both LSM and CAP values. Conclusions: In patients with NAFLD, CAP values should always be taken into account in order to avoid overestimations of liver fibrosis assessed by transient elastography. (Hepatology 2017;65:1145‐1155).